2000
DOI: 10.1093/jn/130.8.1910
|View full text |Cite
|
Sign up to set email alerts
|

Dietary β-Carotene Stimulates Cell-Mediated and Humoral Immune Response in Dogs

Abstract: The role of beta-carotene on immune response in domestic dogs is not known. Female Beagle dogs were fed 0, 2, 20 or 50 mg beta-carotene/d; blood was sampled at wk 0, 1, 2, 4 and 8 for analysis of the following: lymphoproliferation, leukocyte subpopulations and concentrations of interleukin-2 (IL-2), immunoglobulin (Ig)G and IgM. Delayed-type hypersensitivity (DTH) response was assessed at wk 0, 3 and 7. beta-Carotene supplementation increased plasma beta-carotene concentrations in a dose-dependent manner. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 14 publications
3
36
0
1
Order By: Relevance
“…Various reports have demonstrated the use of measuring lymphocyte subsets to investigate immune states in dogs (Blount et al 2005;Greeley et al 2006;Chew et al 2000). It has also been shown that the distribution of peripheral T lymphocyte subsets is impaired in human suffering PDH, both at diagnosis and during the course of the disease (Kronfol et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Various reports have demonstrated the use of measuring lymphocyte subsets to investigate immune states in dogs (Blount et al 2005;Greeley et al 2006;Chew et al 2000). It has also been shown that the distribution of peripheral T lymphocyte subsets is impaired in human suffering PDH, both at diagnosis and during the course of the disease (Kronfol et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In the diabetic dogs, infectious diseases such as conjunctivitis and cystitis are frequently observed accompanying depression of immunocompetence [9]. Lymphocyte subsets have been measured in past various reports to investigate immune states in dogs [2,3,7]. Several studies have shown that distribution of peripheral T lymphocyte subsets are impaired in diabetic humans, both at diagnosis and during the course of the disease [13,15].…”
mentioning
confidence: 99%
“…Analysis of peripheral blood lymphocyte subsets were considered to reflect immune states in dogs [2,3,7]. We considered that the diabetic dogs may have abnormalities of lymphocyte subsets.…”
mentioning
confidence: 99%
“…So, it seems that substances in a carotenoid-like structure such as b-Crp have Ig production-stimulating activity. Chew et al (Chew et al, 2000) reported that a higher concentration of IgG, but not IgM, was found in blood of the bcarotene-administered female Beagle dogs than in nonadministered dogs. The result in this paper is very similar to our data in productions of IgG and IgM, implying that the b-carotene structure might have an effect on the tendency of the Ig productions.…”
Section: Igamentioning
confidence: 96%